An evaluation and comparison of the various statistical and deterministic techniques for forecasting the concentration of criteria air pollutants. (8th February 2011) - Mohan, Manju; Kandya, Anurag; Yadav, Manish
A statistical approach is about working through the historical data in a general way and finding guides to future behaviour. In the present study, forecasting of the criteria pollutants has been done using simple statistical techniques and attempt has been made for an inter-comparison of these techniques with various advanced statistical and deterministic techniques. The inter-comparison analysis leads us to the conclusion that there is no single modelling approach which generates optimum results. Considering the uncertainty and unavailability of most of the inputs of deterministic and advance statistical techniques, the methods adopted here are proposed to have great potential for air pollution forecasting.